STRATEGI PENGEMBANGAN USAHA MADU DI KECAMATAN CAMBA, KABUPATEN MAROS - Hikmah, Aulia Nurul; Astaman, Putra; Dassir, Muhammad; Nadirah, Sitti; Hamsiah, Hamsiah (Jurnal Riset Multidisiplin Agrisosco, 2023)
Camba is one of the area that have a potential business of honey bee in south Sulawesi that should be developed by farmer. The aim of this research was to analyze the business development strategy of honey bee. Data were collected from 30 farmers selected by census, using field observation and direct interview with the respondent using structured questionnaire. This research was conducted in November 2016 until February 2017. The analysis used analytical hierarchy process (AHP). The results of the research indicate that the business development strategy of honey bee in Camba sub district consists of a marketing strategy as a priority and harvesting strategy was the second priority.